PENGARUH VOLUME PENAWARAN SAHAM TERHADAP RISIKO SISTEMATIS DAN IMPLIKASINYA TERHADAP HARGA SAHAM : PENERAPAN DENGAN MODEL REGRESI DATA PANEL COMMON EFFECT (STUDI EMPIRIS PADA SAHAM-SAHAM JAKARTA ISLAMIC INDEX DI BURSA EFEK INDONESIA PERIODE JANUARI - Sunaryo, Sunaryo (Mediastima, 2020)
The purpose of this research was to determine the influence of supply volume stock on the systematic risk and its implications on stock price. This research sample is shared in the sharia category in the JII group (Jakarta Islamic Index) listed on the Indonesia Stock Exchange (IDX) period January-April 2020 by using a saturated sampling method. There were 20 stocks selected as samples. The analytical method used is Path Analysis, the development of panel data regression with common effects. The results of the study showed that the supply volume stock has a significant and negative influence on the stock price. The supply volume stock has a significant and positive influence on the systematic risk. The systematic risk has a significant and negative influence on the stock price. The path analysis results show that systematic risk mediates the effect of supply volume stock on Stock Prices.